2018
DOI: 10.1113/jp275794
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in diaphragmatic fatigue: the cardiovascular response to inspiratory resistance

Abstract: Diaphragmatic fatigue (DF) elicits reflexive increases in sympathetic vasomotor outflow (i.e. metaboreflex). There is some evidence suggesting women may be more resistant to DF compared to men, and therefore may experience an attenuated inspiratory muscle metaboreflex. To this end, we sought to examine the cardiovascular response to inspiratory resistance in healthy young men (n = 9, age = 24 ± 3 years) and women (n = 9, age = 24 ± 3 years). Subjects performed isocapnic inspiratory pressure-threshold loading (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 61 publications
4
69
1
1
Order By: Relevance
“…More recently, we (Welch et al . ) and others (Smith et al . ) have demonstrated that women have an attenuated cardiovascular response to high levels of inspiratory muscle work.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…More recently, we (Welch et al . ) and others (Smith et al . ) have demonstrated that women have an attenuated cardiovascular response to high levels of inspiratory muscle work.…”
Section: Introductionmentioning
confidence: 76%
“…The target pressure selection was based upon previous work (Welch et al . ), where men and women performed inspiratory PTL to task failure. The group mean P di during the task was 98 and 86 cmH 2 O for men and women, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations